Significant neutralizing activities against H2N2 influenza A viruses in human intravenous immunoglobulin lots manufactured from 1993 to 2010 - Kubota-Koketsu, Ritsuko (Dove Medical Press, 2012)
Influenza A H2N2 virus, also known as the Asian flu, spread worldwide from 1957 to 1967, although there have been no cases reported in humans in the past 40 years. A vaccination program was introduced in Japan in the 1960s. Older Japanese donors could have been naturally infected with the H2N2 virus or vaccinated in the early 1960s. Human intravenous immunoglobulin (IVIG) reflects the epidemiological status of the donating population in a given time period. Here, the possible viral neutralizing (VN) activities of IVIG against the H2N2 virus were examined. Hemagglutination inhibition (HI) and VN activities of IVIG lots manufactured from 1993 to 2010 in Japan and the United States were evaluated against H2N2 viruses. High HI and VN activities against H2N2 viruses were found in all the IVIG lots investigated. HI titers were 32–64 against the isolate in 1957 and 64–128 against the isolates in 1965. VN titers were 80–320 against the isolate in 1957 and 1280–5120 against the isolates in 1965. Both the HI and VN titers were higher against the isolate in 1965 than in 1957. Thus, antibody titers of IVIG against influenza viruses are well correlated with the history of infection and the vaccine program in Japan. Therefore, evaluation of antibody titers provides valuable information about IVIGs, which could be used for immune stimulation when a new influenza virus emerges in the human population.